Analisis Rancangan Workshop Sheet Metal Untuk Meningkatkan Keselamatan Dan Efisiensi Kerja di PT. Merpati Maintenance Facility Surabaya - Reno Widyo Wicaksono; Mursyidin; Iwan Engkus Kurniawan (Politeknik Penerbangan Indonesia Curug, 2020)
This study aims to complete the safety management system document and change the layout of the sheet metal workshop at PT. Merpati Maintenance Facility Surabaya. The authors found a decrease in the level of safety and efficiency based on the results of field observations. Based on the existing conditions, the author will process the data using qualitative and quantitative descriptive approaches or HIRAM (Hazard Identification, Risk Assessment and Mitigation) and gap analysis to analyze and process existing data using the HIRAM method which is then followed up by making a new layout. The conclusion of this study is to find the risk of hazards that have a high value so that controls must be carried out to reduce the risk of the hazard to an acceptable level of risk and create a new layout of the sheet metal workshop. Suggestions from the results of this paper are that PT. Merpati Maintenance Facility carries out mitigation measures from the results of this research and makes minimum layout changes as designed by the authors.